DONGENG SEBAGAI ALTERNATIF TKI MENGENALI MASYARAKAT KOREA - Ronidin Ronidin (Puitika, 2017)
This article discusses Korean tales that can be an alternative for Tenaga Kerja Indonesian  (TKI) to recognize Korean society. These fairy tales are literary products that actually reflect the socio cultural reality of Korean society. The tales that are the source of data are download  from the rubric of "Taman Dongeng"  KBS World Radio  in Indonesian language. Through the analysis, it can be said that these tales describe the cultural expression of Korean society such as work ethic, ethics, and religious belief system. This cultural expression needs to be understood by the TKI who will work in South Korea so that they do not a cultural shock experience. Keywords: ethics, fairy tales, Korean society, TKI, work ethics